2018
DOI: 10.1097/mcg.0000000000000787
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Adhesiolysis in Chronic Abdominal Pain

Abstract: In carefully selected patients suffering from chronic abdominal pain, the positive effect of laparoscopic adhesiolysis stands beyond 15 years after the surgery. Although the patients reported relief of pain they still had various abdominal symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…In contrast, other studies have reported that pain reduction does not differ between laparoscopic adhesiolysis and diagnostic laparoscopy alone and therefore they did not recommend laparoscopic adhesiolysis as a treatment for adhesions in patients with chronic abdominal pain [31, 32]. In carefully selected patients with chronic abdominal pain, the positive effects of laparoscopic adhesiolysis can be sustained beyond 15 years after the surgery [33]. In one study, some patients (43%) underwent repeat adhesiolysis because of pain aggravation [14], and it took approximately 6 months for the pain to decrease from an average preoperative score of 8 to a postoperative score of 2 [15].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other studies have reported that pain reduction does not differ between laparoscopic adhesiolysis and diagnostic laparoscopy alone and therefore they did not recommend laparoscopic adhesiolysis as a treatment for adhesions in patients with chronic abdominal pain [31, 32]. In carefully selected patients with chronic abdominal pain, the positive effects of laparoscopic adhesiolysis can be sustained beyond 15 years after the surgery [33]. In one study, some patients (43%) underwent repeat adhesiolysis because of pain aggravation [14], and it took approximately 6 months for the pain to decrease from an average preoperative score of 8 to a postoperative score of 2 [15].…”
Section: Discussionmentioning
confidence: 99%
“…There were no significant differences among the two groups concerning the rate of intraoperative bowel injury, the occurrence of wound infection, or mortality. In a study comparing laparotomy with laparoscopy in 9619 patients with small-bowel obstruction demanding adhesiolysis, Kelly et al described that at 30 days, the patients in the laparoscopic adhesiolysis group had lesser rates of major complications and incisional complications than those in the open group, in addition to decreased mortality (1.3% vs 4.7%) [16] . In a nonrandomized follow-up of 68 patients over 15 years, Paajanen et al determined that adhesiolysis had a long-term positive effect, but even though patients experienced pain relief they still had other abdominal symptoms [17] .…”
Section: Discussionmentioning
confidence: 99%
“…This may require working proximally and distally to the zone of worry before moving toward the reasonable region of hindrance. The reasonable region of deterrent will have enlarged gut proximally and decompressed inside distally [16,19] .…”
Section: Adhesiolysis Technique  Open Approach To Abdominal Adhesionsmentioning
confidence: 99%
“…Thus, laparoscopic adhesiolysis has also become popular and widely studied. [2][3][4][5] In general, the laparoscopic procedure has many benefits compared to open surgery including less postoperative pain, early recovery, and fewer complications in many fields of intra-abdominal surgery. 4,6,7 However, questions remain regarding whether these advantages could be adopted to laparoscopic adhesiolysis for SBO.…”
Section: Introductionmentioning
confidence: 99%